Management of Loose Fruit Sacks at PT. Gunung Sejahtera Dua Indah, Central Kalimantan - Aini, Nurul Faddilah; Nurjanah, Danik; Dinarti, Siwi Istiana (Universitas Galuh, 2025)
This research was conducted at PT. Gunung Sejahtera Dua Indah, Kotawaringin Barat, Central Kalimantan. The aim of this research is to understand the management flow of loose fruit sacks and to gauge the responses of employees involved in the management of loose fruit sacks. This research uses a descriptive method with a qualitative approach, employing primary and secondary company data collected through interviews using questionnaires, observations, and documentation. The data analysis method used is Miles & Huberman’s interactive analysis. The results of this research indicate that (1) The management flow of loose fruit sacks at PT. Gunung Sejahtera Dua Indah in Central Kalimantan is implemented according to the management functions of P-O-A-C (Planning, Organizing, Actuating, and Controling). The responses regarding job responsibilities from the harvesters and the person charge (PIC) of the sacks:harvesters find their tasks enjoyable, while the PIC of the sacks finds the color-coding system for harvesters somewhat challenging.